Cardioprotective effects of naringin in a type 2 diabetes rodent model by reducing calcium overload and oxidative stress - Uryash, Arkady; Mijares, Alfredo; Eltit, Jose Miguel; Adams, Jose A.; Lopez, Jose R. (Frontiers in Pharmacology, 2025)
IntroductionDiabetic cardiomyopathy (DCM) is characterized by structural and functional alterations in the heart muscle, occurring independently of other cardiovascular risk factors such as dyslipidemia, hypertension, or coronary artery disease. Despite efforts to manage type 2 diabetes (T2D) and its complications, DCM remains a significant cause of morbidity and mortality in diabetic patients. The pathogenesis of DCM is multifactorial, involving oxidative stress, inflammation, and intracellular Ca2+ dyshomeostasis. Currently, there is no specific or effective treatment for DCM. Naringin (NRG), a flavonoid abundant in citrus fruits, has demonstrated promising cardioprotective properties.MethodsCardiomyocytes were isolated from a 12-month-old murine T2D model (db/db mice) and corresponding age-matched control subjects. Naringin was administered via intraperitoneal injection at a dosage of 60 mg/kg for 4 weeks to evaluate its cardioprotective efficacy in DCM.ResultsQuiescent cardiomyocytes from db/db mice showed significantly increased diastolic Ca2+ levels ([Ca2+]d), reactive oxygen species (ROS), lipid peroxidation, advanced oxidation protein products (AOPP), and nicotinamide adenine dinucleotide phosphate (NADPH) levels, along with reduced superoxide dismutase (SOD) activity and adiponectin (APN) levels. Plasma markers of cardiac injury were also elevated compared to those in the control group. NRG treatment significantly reduced [Ca2+]d, ROS, lipid peroxidation, AOPP, and NADPH levels while enhancing SOD activity and APN levels. Furthermore, NRG attenuated plasma cardiac injury markers in db/db mice.ConclusionThe results of this study illustrate the cardioprotective potential of NRG in diabetic cardiomyopathy by mitigating intracellular calcium overload and oxidative stress, augmenting antioxidant defenses, and reducing cardiac injury. NRG could serve as a promising adjunctive therapeutic approach to enhance cardiac function in diabetic patients.